Auraptene suppresses inflammatory responses in activated RAW264 macrophages by inhibiting p38 mitogen‐activated protein kinase activation. Issue 7 (14th March 2013) - Lin, Shan; Hirai, Shizuka; Goto, Tsuyoshi; Sakamoto, Tomoya; Takahashi, Nobuyuki; Yano, Masamichi; Sasaki, Takao; Yu, Rina; Kawada, Teruo
Abstract : Scope: Inflammation plays a key role in obesity‐related pathologies such as insulin resistance and type 2 diabetes. Hypertrophied adipocytes trigger the enhancement of macrophage infiltration and the release of various proinflammatory factors in obese adipose tissue. In this study, we examined whether auraptene, a citrus‐fruit–derived compound, could suppress the production of inflammatory factors that mediate the interaction between adipocytes and macrophages. Methods and results: Experiments using a co‐culture system of 3T3‐L1 adipocytes and RAW264 macrophages showed that auraptene reduced the production of nitric oxide and tumor necrosis factor‐α. In RAW264 macrophages, auraptene also suppressed the inflammation induced by either LPS or the conditioned medium derived from 3T3‐L1 adipocytes. In addition, auraptene inhibited the phosphorylation of the p38 mitogen‐activated protein kinase and suppressed the production of proinflammatory mediators in activated macrophages. Conclusion: Our findings indicate that auraptene exhibits anti‐inflammatory properties by suppressing the production of inflammatory factors that mediate the interaction between adipocytes and macrophages, suggesting that auraptene is a valuable food‐derived compound with a potential to attenuate chronic inflammation in adipose tissue and to improve obesity‐related insulin resistance.